Mathematical model for a compressed air system that couples demand and supply. (16th December 2021) - Thabet, Mohamad; Sanders, David; Tewkesbury, Giles
This paper presents a mathematical model for a compressed air system (CAS) that couples system supply and demand. The supply side contains components responsible for production, treatment and storage of compressed air, while the demand side contains components that deliver and consume compressed air. Components considered include compressor, cooler, storage tank, linear actuators and an air blower. Simulations were performed to study the impact of pressure regulation and storage tank size on system energy consumption. Results showed that pressure regulation reduced air and energy consumption and a properly sized tank volume reduced energy consumption while maintaining good system pressure stability.